Identification of Atypical Enteropathogenic Escherichia coli O98 from Golden Snub-Nosed Monkeys with Diarrhea in China - Qi, Mingpu; Wang, Qiankun; Tong, Shengtao; Zhao, Gang; Hu, Changmin; Chen, Yingyu; Li, Xiang; Yang, Wanji; Zhao, Yuchen; Platto, Sara; Duncan, Robertson Ian; Chen, Jianguo; et al. (Frontiers in Veterinary Science, 2017)
Fecal samples (n = 76) were collected from 38 snub-nosed monkeys (Rhinopithecus roxellanae) in Shennongjia National Nature Reserve (China) and examined for the presence of enteropathogenic Escherichia coli (EPEC). The 56 samples originated from 30 free-ranging monkeys on the reserve and 20 samples from 8 captive monkeys that were previously rescued and kept at the research center. Eight diarrhea samples were collected from four of the eight captive monkeys (two samples from each monkey), and two EPEC strains (2.6%) (95% confidence interval [CI] 0.3%, 9.2%) were isolated from two fecal samples from two diarrheic monkeys. Both strains belonged to serotype O98 and phylogenetic group D (TspE4C2+, ChuA+). The virulence gene detection identified these strains as an atypical EPEC (aEPEC) (bfpB–, stx1–, and stx2–) with the subtype eae+, escV+, intimin+. These strains were highly sensitive to all the antibiotics tested. The 50% mouse lethal dose (LD50) of the two isolates in Kunming mice was 7.40×108 CFU/0.2 mL and 2.40×108 CFU/0.2 mL, respectively, indicating low virulence. Based on the report that this serotype had been isolated from some other non-human animals and humans with diarrhea, the first identification of aEPEC O98 strains and their drug resistance profile in R. roxellanae is of ecological significance for disease control in this endangered species.